2017
DOI: 10.1183/13993003.02505-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating 17 years of latent tuberculosis infection screening in north-west England: a retrospective cohort study of reactivation

Abstract: Approximately 72% of tuberculosis (TB) cases in England occur among non-UK born individuals, mostly as a result of reactivation of latent TB infection (LTBI). Programmatic LTBI screening is a key intervention of the TB strategy for England. This article reviews the results of a long-standing LTBI screening initiative in England.A retrospective cohort was created through probabilistic linkage between LTBI screening data and national TB case notifications. Screened persons were followed until they died, became a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…A study from the UK conducted in recent migrants from high TB incidence areas demonstrated that among migrants with LTBI, those who had LTBI treatment based on a positive IGRA had a significantly reduced risk of TB during the observation period compared with untreated LTBI-positive patients (incidence rate ratio 0.17, 95% CI 0.05-0.60) [38].…”
Section: Screening For Ltbimentioning
confidence: 99%
“…A study from the UK conducted in recent migrants from high TB incidence areas demonstrated that among migrants with LTBI, those who had LTBI treatment based on a positive IGRA had a significantly reduced risk of TB during the observation period compared with untreated LTBI-positive patients (incidence rate ratio 0.17, 95% CI 0.05-0.60) [38].…”
Section: Screening For Ltbimentioning
confidence: 99%
“…In most cases, addressing the underlying factors are perceived as complementary rather than the fulcrum around which efforts to eliminate TB should revolve [ 17 , 18 ]. While improvement in existing tests are necessary and would contribute to minimising TB reactivation among high risk groups [ 19 ], there are debates about the accuracy of the existing screening tests to predict progression from LTBI to active TB [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…25 The epidemiology of TB in England supports the notion that LTBI treatment could be of great benefit for recent immigrants from countries with high TB burden. 2,[26][27][28] In our cohort, none of the participants that were screened for LTBI developed active TB within the observed time period, potentially indicating the benefit of this intervention to reduce the number of incident TB cases. However, our results indicate that the effectiveness of this intervention might be affected by low attendance to primary care, as only half of the eligible new-entrant migrants registered in primary care.…”
Section: Discussionmentioning
confidence: 99%